Sistem Pendukung Keputusan untuk Pemilihan Rumah Kos Terbaik di Kecamatan Mlati, Kabupaten Sleman - Kartikadyota Kusumaningtyas; Ayu Dewi Nurullatifah; Natalia Dwi Cahyani (Jurnal Dinamika Informatika, 2020)
In line with the large number of newcomers in Special Region of Yogyakarta, there have been many requests for boarding houses around the campus area. One sub-district that is geographically close to several universities is Mlati Subdistrict, Sleman Regency. Types of boarding houses are various, ranging from location, rental prices, and others. There are many types of boarding houses, ranging from locations, rental prices, and others. If someone feels uncomfortable with his/her boarding house, then he/she will often move around. Some of the reasons are: the more expensive rental rates, facilities, looking for other boarding houses that are closer to campus, and safety factor. Therefore, we developed a decision support system that can give an information about the best boarding house according to someone's need. It was created by applying the Simple Additive Weighting (SAW) method. The SAW method will generate a preference value. The alternative which has the greatest preference value will be chosen as the best alternative. The test results show that there is a correspondence between the value produced by the system and the value generated by manual calculations. Thus, the decision support system has successfully implemented SAW method and is able to function as its functions.